C54 METABOLIC SYNDROME IN HEART TRANSPLANTATION: AN UNDERESTIMATED RISK FACTOR?. (18th May 2022) - Ferrara, V; Sponga, S; Marinoni, M; Valdi, G; Di Nora, C; Nalli, C; Benedetti, G; Lechiancole, A; Parpinel, M; Livi, U
Abstract: Background and Aims: Metabolic Syndrome (MS) is a multifactorial condition that increases the risk of cardio–vascular events, it's frequent in Heart transplant (HTx) candidates and worsens with immunosuppressive therapy. Aim of the study was to analyse the impact of MS on long–term outcome of HTx patients in our centre. Methods: MS was defined through the presence of at least 3 of the following factors: Triglyceride ≥150mg/dl or drug treatment for hypertriglyceridemia HDL <40mg/dl for men and <50mg/dl for women Blood glucose ≥100mg/dl or diabetes mellitus Arterial pressure ≥130/80 or hypertensive drug treatment BMI>30. In 349 HTx patients since 2007, mortality and morbidity predictors were evaluated. Results: MS was present in 35% of patients pre–HTx and 47% within the first year of follow–up. Five–year survival in patients with pre–HTx MS was worst (65% vs 78%, p < 0.01), as well as in those with MS in the first year of follow–up (78% vs 89%, p < 0.01). At the univariate analysis, risk factors for mortality were recipient age (HR 1.07, 1.04–1.09, p < 0.01), pre–HTx MS (HR 1.86, 1.29–2.69, p < 0.01), pre–HTx hypertension (HR 2.46, 1.70–3.55, p < 0.01), pre–HTx hypertriglyceridemia (HR 1.50, 1.04–2.18, p = 0.03), chronic renal failure (HR 2.95, 2.03–4.27, p < 0.01), MS and diabetes at 1–year follow–up (HR 2.00, 1.25–3.19, p < 0.01; HR 2.02, 1.27–3.23, p < 0.01, respectively). The last two resulted also risk factors for CAV (HR 1.86, 1.16–2.99, p = 0.01; HR 1.67, 1.03–2.69, p = 0.04, respectively). MS at 1–year follow–up determined a significant higher risk to develop CAV at 5– and 10–year follow–up, compared to patients without MS (25% vs 14% and 44% vs 25%, p < 0.01). Conclusions: MS is an important risk factor for both mortality and morbidity post–HTx, suggesting the need for a strict monitoring of metabolic disorders with a careful nutritional follow–up in HTx patients.